Of the cavitation effect in a francis type hydraulic turbine under operating conditions at operating conditions of the Chaglla - Limachi Viamonte, Wilhem Rogger (2024)
The performance of a hydropower plant depends on several parameters, i.e., the turbine type used, plant design, turbine classification, plant head, flow rate. All turbines are used for their best operation under the best level of efficiency with optimal values for their nominal head, water flow and turbine speed. However, under these conditions, the cavitation phenomenon occurs in the hydraulic turbine. It is only for the reason that the dynamic attribute of liquid flow becomes unstable with high pressure fluctuations. Cavitation is an unavoidable and unavoidable problem in hydraulic turbines. Cavitation destroys the performance of the turbines. When turbines operate at partial loads rather than their highest efficiency point, they experience cavitation to a greater extent. Francis turbines are designed to be operated in various conditions. The research objective was to analyze the cavitation occurrence in a Francis type turbine and how to minimize it, as a result a report was obtained on damages caused by the bubbles implosion on the surfaces of the turbine, especially in the impeller, at the exit waist edge of the intermediate zone in UG-1, present areas with cavitation wear between blade and blade 1-2. 3-4. 8-9. 11-12. 13-1. According to the inspection, the evolution of the cavitated areas is controlled and a slight detachment of material is observed, which does not compromise the useful life of the impeller. Likewise, for the impeller blades in the UG-2, cavitation wear areas occur between blade and blade 3-4. 9-10. 11-12; It is also controlled and slight material release is observed which does not compromise the useful life of the impeller. Regarding the wear of the blades in the impeller, we can indicate that in the UG2 there is 6.47 % accumulated wear, while in the UG1 there is 5.47 %. In the case of the guide vanes, the wear clearance with the highest incidence is in the UG2 with 0.692 mm of accumulated wear, while in the UG1 with 0.2595 mm.